Continuing Nuclear Data Research for Production of Accelerator-Based Novel Radionuclides for Medical Use: A Mini-Review - Qaim, Syed M.; Hussain, Mazhar; Spahn, Ingo; Neumaier, Bernd (Frontiers in Physics, 2021)
Nuclear data are important for production and medical application of a radionuclide. This brief review concentrates on nuclear reaction cross-section data. The availability of standardised nuclear data for accelerator-based production of medical radionuclides is outlined. Some new directions in radionuclide applications, e.g. theranostic approach, bimodal imaging, radionuclide targeted therapy, etc., are considered and the status of relevant nuclear data is discussed. The current trends in nuclear data research using accelerators are elaborated. The increasing significance of intermediate energy accelerators in production of therapeutic radionuclides is emphasised.